Getting used to learning with the iPad: a learner's journey - Gabarre, Cecile; Gabarre, Serge; Din, Rosseni; Shah, Parilah; Abdul karim, Aidah (2012)

(untitled)
The past two years have seen the demand for tablet computers arose worldwide with Malaysia standing among the largest growing tablet markets in South-East Asia. The students’ ownership of tablet computers is therefore expected to follow this general trend. Previous observations with foreign language undergraduates revealed that the number of students with tablet computers grew with every new intake. This leads to implications regarding future m-learning potential applications for higher education. The first issue concerns the learners’ literacy and ability to adapt to learning with tablet computers. The second is to explore the learners’ usage of these devices in education. This research sought to understand the technical and pedagogical implications for the learners willing to use tablet computers in their French as a foreign language class. A qualitative case study design with a narrative method of inquiry was conducted to explore the technical and learning potentials as well as the challenges associated with tablet computers as experienced by a learner.